FROM SOCIAL MEDIA CAPITAL TO ENTREPRENEURIAL DIFFUSION: THE ROLE OF MARTECH E-COMMERCE EMPOWERMENT AMONG YOUNG ENTREPRENEURS - Hsin-Hui Lin (PUPIL: International Journal of Teaching, Education and Learning, 2026)
In recent years, the government has actively encouraged young people to participate in entrepreneurial activities by providing relevant subsidy programs. At the same time, a new wave of MarTech has swept across the globe, prompting many brick-and-mortar stores to transition to e-commerce platforms. Consequently, online shopping has become increasingly prevalent and has expanded across a broader range of age groups. Both consumers and entrepreneurs conduct transactions through e-commerce platforms. Focusing on young entrepreneurs, this study draws on social media theory, MarTech, and e-commerce empowerment theory to investigate their entrepreneurial behaviors, including idea generation, practice, and diffusion. Data were collected through a self-administered questionnaire and analyzed using SPSS 24.0 and SmartPLS 4.0. The analyses included descriptive statistics, reliability and validity assessments, and structural equation modeling. The results indicate that, within the social commerce environment, young entrepreneurs’ cognitive social media capital has no significant effect on any of the three dimensions of MarTech e-commerce empowerment, namely marketing technology utilization, personal leadership, and online community interaction. However, their structural social media capital significantly influences marketing technology utilization and personal leadership. Furthermore, their relational social media capital exerts stronger effects on all three dimensions of MarTech e-commerce empowerment. In addition, the personal leadership dimension of MarTech e-commerce empowerment significantly influences young entrepreneurs’ idea generation, practice, and diffusion behaviors. The theoretical model developed in this study not only provides an in-depth examination of how social media capital affects the behaviors of young entrepreneurs but also further clarifies the critical mediating role of MarTech e-commerce empowerment in the entrepreneurial process. In terms of practical applications, the findings can help young entrepreneurs use social media capital more effectively, enhance their marketing technology capabilities and leadership, and strengthen online community interaction and engagement, thereby facilitating entrepreneurial behaviors. The findings also provide policymakers, academic researchers, and relevant industries with insights into developing more comprehensive entrepreneurial support mechanisms. The results of this study offer important implications for the theoretical and practical development of youth e-commerce entrepreneurship education.